Efektivitas Haloperidol-Difenhidramin sebagai Terapi Agitasi Akut pada Pasien Skizofrenia: Narrative Review - Rahmawati, Fita; Medisusyanti, Amalia Suci; Yoga, Bambang Hastha; Oktasari, Sholikhah Rosvita (Jurnal Skala Kesehatan, 2025)
Schizophrenia psychiatric disorder is characterized by the emergence of delusions, hallucinations, and the inability to distinguish between reality and fantasy. In the acute phase, people with schizophrenia can experience agitation that can endanger themselves and those around them. Rapid-acting antipsychotics with minimal side effects are needed in treating acute agitation in schizophrenia patients. Haloperidol is a first-generation antipsychotic that acts on dopamine D2 receptors, which helps reduce positive and negative symptoms. Haloperidol has been widely used for the treatment of acute agitation because of its rapid effects, but the prevalence of extrapyramidal symptoms is relatively high. Diphenhydramine is an antihistamine with anticholinergic activity used to treat extrapyramidal symptoms. Several guidelines recommend the use of diphenhydramine as a pharmacological therapy for extrapyramidal symptoms, but in practice, psychiatry provides diphenhydramine together with haloperidol as prophylaxis. This combination helps treat acute agitation, where haloperidol can reduce symptoms of schizophrenia, and diphenhydramine can provide sedation and treatment of extrapyramidal symptoms. The challenge in managing acute agitation in schizophrenia patients continues due to drug side effects. A better understanding of the pathophysiology of schizophrenia is expected to produce effective pharmacological therapy alternatives in treating acute agitation